2012
DOI: 10.1128/aac.00700-11
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Safe and Orally Effective 4-Aminoquinaldine Analogues as Apoptotic Inducers with Activity against Experimental Visceral Leishmaniasis

Abstract: Novel antileishmanials are urgently required to overcome emergence of drug resistance, cytotoxic effects, and difficulties in oral delivery. Toward this, we investigated a series of novel 4-aminoquinaldine derivatives, a new class of molecules, as potential antileishmanials. 4-Aminoquinaldine derivatives presented inhibitory effects on L. donovani promastigotes and amastigotes (50% inhibitory concentration range, 0.94 to 127 M). Of these, PP-9 and PP-10 were the most effective in vitro and demonstrated strong … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…The reduced formazan, which is a measure of cell viability, was dissolved in dimethyl sulfoxide. The absorbance at 550 nm was measured in a spectrophotometer (Hitachi Electronics, Japan) (24).…”
mentioning
confidence: 99%
“…The reduced formazan, which is a measure of cell viability, was dissolved in dimethyl sulfoxide. The absorbance at 550 nm was measured in a spectrophotometer (Hitachi Electronics, Japan) (24).…”
mentioning
confidence: 99%
“…Compound 1 resulted in a nearly twofold increase in ROS levels with respect to control culture at 3 h (MFI: control 232.24, treatment 481. [21] GSH is also important for protecting the parasites from ROS and other toxic compounds. Hydrogen peroxide, as a positive control, increased ROS levels in promastigotes relative to compound 1 (3.5-fold; Figure 6 a).…”
Section: Induction Of Oxidative Stress and Decreased Intracellular Gsmentioning
confidence: 99%
“…Both the compounds did not cause any changes in haematological or cardiac functions in BALB/c mice and were not hepato or nephrotoxic. Investigation of their mode of action revealed that killing by PP-10 involved moderate inhibition of dihydrofolate reductase and elicitation of the apoptotic cascade 79 .…”
Section: Investigational Drugsmentioning
confidence: 99%